Monsoon rainfall variability and rainfed agriculture in the water-scarce Karha Basin, western India - TODMAL, RAHUL S.; KALE, VISHWAS S. (MAUSAM, 2016)
Recent climate projection models indicate that the semi-arid regions of the world are most vulnerable to the impact of climate change. Hence, the understanding of rainfall variability and availability of water resources in water-scarce regions is crucial for planners to formulate annual plan for judicious utilization and distribution of water. In the present study, an attempt is made to evaluate the hydro-meteorological characteristics of the Karha Basin, located in the rain shadow zone of the Western Ghat. Trends in monsoon rainfall, dam storage and the area under some principal crops were analyzed to ascertain their interrelationship. The analyses indicate high inter-annual variability in monsoon rainfall and distinct episodes of above - and below-average monsoon rainfall. There is enough evidence for enhanced monsoon variability during the recent decades and a tendency for weaker monsoons to be associated with El Niño events. The study also provides evidence of changes in the area under major crops with the multi-year fluctuations in monsoon rainfall and dam water storage. The relationship, however, is not as strong as expected and the pattern gets more erratic and confusing in the most recent decades, partly on account of increasing dependence on irrigation. The Karha Basin is already suffering from severe water scarcity. Increasing monsoon variability, seasonality and dependence on groundwater is likely to threaten agriculture and food security. Climate change related impacts are likely to further add to already difficult water management challenges in the basin. It is therefore necessary to plan for new challenges under climate change scenarios.